Institutional Effects of Higher Education Acquisitions: The Case of Texas A&M School of Law - Austin Lyke (SAGE Publishing, 2018)
This study analyzes the acquisition of the Texas Wesleyan University School of Law by Texas A&M University. In particular, institution-level effects are examined by measuring selectivity, tuition prices, job outcomes, and bar passage rate before and after the law school changed names from a hyperregional institution to one of statewide eminence and national recognition. Difference-in-differences estimations and synthetic control analysis are used to measure effects of the acquisition on various institutional metrics. Results show an increase on school selectivity and null effects on tuition price and job outcomes, suggesting heterogeneity in response to the acquisition. Implications for higher education and legal education, specifically, are discussed.